(untitled) (Journal of Information Technologies in Education (ITE), 2018)
The article deals with the issue of the effectiveness of using a virtual laboratory practice on the physiology of humans and animals in the structure of the training of a future specialist biologist instead of a real model object in laboratory work. We are witnessing the increasing involvement of interactive learning tools, implemented with the use of educational computer programs, including for the organization of practical and laboratory classes. Based on the questionnaire of biologists who previously performed laboratory work with both a real model object and a virtual one, it was found that the replacement of the actual object of laboratory work on the virtual does not contribute to a better assimilation of the basic concepts of human physiology and animals It is expedient to use a virtual laboratory practice only in cases where there is no material opportunity to conduct the experiment, the phenomenon under investigation cannot be reproduced within the framework of the training laboratory or it proceeds under conditions that it is difficult to observe (for example, in very short time limits). The introduction of a virtual laboratory workshop in its pedagogical activity is the choice of every teacher personally, but one cannot forget that the overeating of the use of interactive methods and the inappropriate replacement of a virtual object virtual may lead to the loss of the didactic and educational goal of learning.